Transgenic mice overexpressing Pitx2 in the atria develop tachycardia-bradycardia syndrome - Shunsuke Baba; Satoko Shinjo; Daiki Seya; Hiroki Bochimoto; Toru Akaike; Atsushi Nakano; Susumu Minamisawa (PLoS ONE, 2025)
Sinoatrial node (SAN) dysfunction often accompanies supraventricular tachyarrhythmias such as atrial fibrillation (AF), which is referred to as tachycardia-bradycardia syndrome (TBS). Although there have been many studies on electrical remodeling in TBS, the regulatory mechanisms that cause electrical remodeling in the SAN and atrial muscles by chronic bradycardia or tachycardia have not yet been fully investigated. Here we hypothesized Pitx2c, a transcription factor that played a central role in the late aspects of left-right asymmetric morphogenesis, regulated an interrelationship between the SAN and the atrial muscles and was involved in TBS-like pathology. To test this hypothesis, we generated transgenic mice overexpressing Pitx2c specifically in the atria (OE mice). Although Pitx2c is normally expressed only in the left atria (LA), the expression levels of Pitx2c protein in the right atria (RA) were significantly increased to similar levels of those in the LA of non-transgenic control mice (WT). We found the heart rate of OE mice was significantly variable although the average heart rate was similar between WT and OE mice. Electrophysiological examination showed OE mice exhibited prolonged SAN recovery time and higher AF inducibility. Histological analysis revealed SAN-specific ion channel HCN4-positive cells were hardly detected in the SAN of OE mice, along with ectopic expression in the RA. Furthermore, transcription factors associated with SAN formation were down-regulated in the RA of OE mice. We conclude that SAN dysfunction by Pitx2 dysregulation predisposed OE mice to a TBS-like phenotype, and Pitx2c is a key regulator that defines SAN function in the atria.